Quantitative study of lubricant depletion mechanism for heat-assisted magnetic recording (HAMR) - Chong, Kok Weng. (2012)
Heat Assisted Magnetic Recording (HAMR) is an innovative technology which enables large increase in the storage density of hard disc devices. With regards to this latest technology, it has been suggested that there exists a critical head-disk-interface (HDI) issue which associated with the use of ultrathin liquid lubricant films on the disk surface. This problem is credited to the fact that these films are heated to high temperatures by using laser beams in order to reduce its magnetic coercivity. Experimental studies of the lubricant depletion under laser irradiation are still very limited so far. In this thesis, quantitative study of lubricant depletion under HAMR condition will be carried out. In order to have a better understanding of lubricant depletion under HAMR condition, first, a uniform lubricant layer sample will be prepared by using dip coating process. Then, the disk with uniform lubricant will be heated by a laser which will cause lubricant to deplete. After the laser test, the disk surface will be scanned with OSA (optical surface analyzer) to evaluate lube depletion quantitatively in order to determine the amounts of lube depletion, accumulation and lube permanent loss. In this thesis, the effect of laser heating power and effect of total laser on time on lubricant depletion will also be studied experimentally on a self-developed HAMR tester. It is found that lubricant depletion under laser heating is more severe if a higher laser power is used. In addition, the experiment also shows that the shorter the total laser on time, the less severe lubricant depletion, accumulation, loss and depletion depth.